Patients with Chronic Lymphocytic Leukemia are more Likely to Have TP53 Gene Mutations - Sheeba Faryal, Rabia Shahbaz, Mahesh Kumar Luhano, Huria Huma, Nosherwan Babar, Faizan Ahmed (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose was to quantify the prevalence of Tp53 gene mutation in chronic lymphocytic leukemia patients.. Study Design: Cross-sectional/ Descriptive study Place and Duration: This study was conducted in multiple centres including Mayo Hospital Lahore and Liaquat University of Medical and Health Sciences in the duration from August, 2022 to January, 2023. Methods: Total 112 cases of chronic lymphocytic leukaemia were included in this study. All the patients were received at laboratory for TP53 mutation analysis. To identify the TP53 mutation using the FISH method, five ml of whole blood or one ml of bone marrow aspirate sample were taken. Data input and analysis were done with the help of the statistical package for social sciences 22. Results: The mean age of the patients was 52.8±6.52 years and had mean BMI 23.7±14.52 kg/m2. Seventy-three (65.2%) patients were males and 39 (34.8%) cases were females. There were 52 (46.4%) patients educated and 60 (53.6%) cases were non educated. We found frequency of Tp53 gene mutation in 17 (15.2%) cases in which 11 cases were males and 6 cases were females. Among 17 cases of Tp53 gene mutation, 8 cases had age >50 years, 6 cases were aged between 30-50 years and 3 cases were between 18-30 years. Conclusion: We concluded in this study that frequency of Tp53 gene mutation in patients of chronic lymphocytic leukaemia was 15.2% in which majority were males and had age >50 years. Keywords: CLL, Tumour suppressor gene, Chronic lymphocytic leukaemia, FISH, TP53, Fluorescence in Situ hybridization